Characteristics of bed forms and regimes of flow in alluvial channels - Garde, R. J., author; Albertson, Maurice L., author; Civil Engineering Section, Colorado State University, publisher (Colorado State University. Libraries, 1959)
The characteristics of the bed and the water surface in an alluvial channel are changed by changing the characteristics of the flow, the fluid, and/or the sediment. This paper first reviews the existing literature on the characteristics of bed forms and regimes of flow over an alluvial bed and then it reports the studies made by the writers about the scale of ripples and dunes and about the criteria for the prediction of different regimes of flow in an alluvial channel.
CER59RJG9.
Keywords: Alluvial streams; Sediment transport